Pedagogical Leadership in Higher Education: A Systematic Review - Nále Castelar García Quispe; Luis Miguel Romero Echevarria; Georgina Alejandrina Pinto Sotelo; Luis Alberth Rossel Bernedo; Huisa Huahuasoncco Martin William (International Journal of Medical Toxicology and Legal Medicine, 2024)
Pedagogical leadership in higher education emerges as an essential component to improve teaching and learning. The study was based on pure research, qualitative approach, systematic review and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (Prisma) statement. The research showed that, although pedagogical leadership promotes a teaching and learning environment for the higher education community, it faces a series of challenges and obstacles such as lack of understanding of leadership and lack of financial support from institutions. Thus, it was concluded that pedagogical leadership plays a crucial role in the development of educational practices that respond to contemporary demands; however, pedagogical practice must institutionalize innovation, focus on reflection and adapt strategies centered on learning and applicable to professional life.